Electrical Contacts - 1997 Proceedings of the Forty-Third IEEE Holm Conference on Electrical Contacts
DOI: 10.1109/holm.1997.637868
|View full text |Cite
|
Sign up to set email alerts
|

Intermittence detection in fretting corrosion studies of electrical contacts

Abstract: The occurrence of intermittences in electrical circuits can result in serious reliability problems particularly where low signal voltages and currents are used. It is well known that differential thermal expansion or vibration in electrical connectors can result in micromotion resulting in fretting corrosion. This can lead to an increase in contact resistance and eventual loss of electrical contact. The occurrence of electrical intermittences has been considered a precursor to contact failure associated with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 8 publications
0
16
1
Order By: Relevance
“…Contrary to the results presented by Abbott et al [3], [4] and Murrell et al [5] the contact resistance decreases in the experiments presented here above approximately 200 fretting cycles to values that are expected for new contacts. An elemental analysis of the contact areas reveals that the tin-plating starts to wear through after about 100 fretting cycles and is completely worn through after about 600 cycles.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the results presented by Abbott et al [3], [4] and Murrell et al [5] the contact resistance decreases in the experiments presented here above approximately 200 fretting cycles to values that are expected for new contacts. An elemental analysis of the contact areas reveals that the tin-plating starts to wear through after about 100 fretting cycles and is completely worn through after about 600 cycles.…”
Section: Discussioncontrasting
confidence: 99%
“…Abbott et al [3], [4] and Murrell et al [5] detect intermittences using counters and Hübner-Obenland et al [6] measure the contact resistance profile during intermittences. Skinner [7] and Malucci [8] investigate the topic theoretically.…”
Section: A Intermittences-reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Field data has shown that between 30-60% of electrical failures are attributed to connector problems [2], [3]. A typical failure is defined as a high contact resistance or intermittent contact resistance faults [4], [5]. The degradation mechanisms, which lead to a high contact resistance, have been extensively investigated over many years; this has resulted in accelerated simulated tests to aid in connector design and verification of performance [6]- [11].…”
mentioning
confidence: 99%
“…2008.2001162 connector systems where the conduction path across the electrical contact interface is disrupted for a short duration [2]- [5]. These events can cause difficulties with electronic systems and result in system failure.…”
Section: Introductionmentioning
confidence: 99%